Probiotic Potential Analysis and Safety Evaluation of Enterococcus durans A8-1 Isolated From a Healthy Chinese Infant - Zhou, Yi; Shi, Lu; Wang, Juan; Yuan, Jia; Liu, Jin; Liu, Lijuan; Da, Rong; Cheng, Yue; Han, Bei (Frontiers in Microbiology, 2021)
To evaluate the probiotic characteristics and safety of Enterococcus durans isolate A8-1 from fecal sample of healthy Chinese infant. We determined the tolerance to low pH, survival in bile salts and NaCl, adhesion ability, biofilm formation, antimicrobial activity, toxin gene distribution, hemolysis, gelatinase activity, antibiotic resistance, and virulence to Galleria mellonella, and interpreted the characters by genome re-sequencing. Phenotypically, E. durans A8-1 survived at pH 5.0, in 7.0% NaCl and 3% bile salt under aerobic and anaerobic condition. The bacterium had higher adhesion ability toward mucin, collagen, and BSA in vitro, and showed high hydrophobicity (79.2% in chloroform, 49.2% in xylene), auto-aggregation activity (51.7%) and could co-aggregate (66.2%) with S. typhimurium; It had adhesion capability to intestinal epithelial Caco-2 cells (38.74%) with moderate biofilm production, and antimicrobial activity against several Gram-positive pathogenic bacteria. A8-1 can antagonize the adhesion of Salmonella typhimurium ATCC14028 on Caco-2 cells to protect the integrity of cell membrane by detection of LDH and AKP activities. A8-1 also helps the cell relieve the inflammation induced by lipopolysaccharide by reducing the expression of cytokine IL-8 (P=0.002) and TNF-α (P>0.05) and increasing the IL-10 (P<0.001). For the safety evaluation, A8-1 showed no hemolytic activity, no gelatinase activity, and had only asa1 positive in the 7 detected virulence genes in PCR, while it was not predicted in the genome sequence. And it was susceptible to benzylpenicillin, ampicillin, ciprofloxacin, levofloxacin, moxifloxacin, tigecycline, nitrofurantoin, linezolid, vancomycin, erythromycin, quinupristin / dalofopine except clindamycin, which was verified by the predicted lasA, lmrB, lmrC and lmrD genes contributed to the clindamycin-resistance. The virulence test of G. mellonella showed that it had toxicity lower than 10% at1×107 CFU. According to the results of these evaluated attributes, E. durans strain A8-1 could be a promising probiotics candidate for applications.